Stem cell transplantation in neurological diseases: improving effectiveness in animal models - Adami, Raffaella; Scesa, Giuseppe; Bottai, Daniele (Frontiers in Cell and Developmental Biology, 2014)
Neurological diseases afflict a growing proportion of the human population. There are two reasons for this: first, the average age of the population (especially in the industrialized world) is increasing, and second, the diagnostic tools to detect these pathologies are now more sophisticated and can be used on a higher percentage of the population. In many cases, neurological disease has a pharmacological treatment which, as in the case of Alzheimer's disease, Parkinson's disease, Epilepsy, and Multiple Sclerosis can reduce the symptoms and slow down the course of the disease but cannot reverse its effects or heal the patient. In the last two decades the transplantation approach, by means of stem cells of different origin, has been suggested for the treatment of neurological diseases. The choice of slightly different animal models and the differences in methods of stem cell preparation make it difficult to compare the results of transplantation experiments. Moreover, the translation of these results into clinical trials with human subjects is difficult and has so far met with little success. This review seeks to discuss the reasons for these difficulties by considering the differences between human and animal cells (including isolation, handling and transplantation) and between the human disease model and the animal disease model.